Corporate philanthropy - Campbell, David (Henry Stewart Talks, 2011)
Definitions, Mechanisms of philanthropy, History of philanthropy, Generosity ratio, Motivations for philanthropy, The agency problem, The ethical debate about corporate philanthropy, Strategic philanthropy